In-situ hybridization of graphene sheets onto polyaniline nanofiber arrays grown on the surface of carbon cloth under high electric voltage field for high–performance flexible supercapacitor. (March 2020) - Shen, Yueying; Qin, Zongyi; Hu, Shuo; Yang, Lifeng; Xu, Xian; Ding, Lei; Zhang, Youwei
Abstract: Two kinds of free–standing flexible hybrid electrode materials were fabricated through in situ hybridization of graphene oxides (GOs) onto polyaniline (PANI) nanofiber arrays grown on the surface of carbon cloth under high voltage electric field. The GOs introduced to the arrays could act as the growth sites or the top layer on the PANI arrays, depending on the spraying order of the GO before and after aniline. Great improvement in charge storage ability of PANI nanofibers could be achieved especially by using the GO as the substrate for the growth of the arrays. The PANI/GO/CC electrode showed a maximum areal capacitance of 1122.8 mF cm −2 at the scan rate of 5 mV s −1 . Assembled with these electrodes, the all–solid–state symmetric supercapacitor could deliver a maximum energy density of 46.6 μWh cm −2 at a power density of 498.9 μW cm −2 with high capacitance retention of 94.1% and mechanical flexibility. The excellent capacitive performances could be ascribed to unique structural advantages of PANI nanofiber array enhanced by synergetic effect between PANI and graphene sheets. Such in situ hybridization could provide a facile and scalable route for fabricating high–performance free–standing flexible electrode materials for foldable and wearable devices. Graphical abstract: Image 104 Highlights: In situ hybridization of GO and PANI during the growth of PANI nanofiber array under high voltage electric field. Great improvement in charge storage ability of PANI achieved especially by introducing graphene sheet to the bottom of the array. The maximum energy density of 46.6 μWh cm −2 at a power density of 498.9 μW cm −2 with the capacitance retention of 94.1% for the assembled devices.